Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this and **thousands** of other questions.

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this and **thousands** of other questions

can you find g(-5) = ????

after you find g(-5), put that answer into f...

yes... but i only wanted g(-5)... so g(-5) = -4*(-5) + 3 = ????
what's the answer here?

23

good... now that you found g(-5)=23, that 23 goes into f. so you need to find f(23) = ???

It would be -53 wouldnt it?

that is the definition of (f ° g)(-5) = f(g(-5))

yes.... :)
f(23) = -2*(23) - 7 = -46 -7 = -53

good work... :)

Thanks for your help.! =)

yw...:)